Screening for developmental delay among children aged 1-4 years: a systematic review - Warren, Rachel (CMAJ Open, 2016)
BACKGROUND: Existing guidelines on screening children less than 5 years of age for developmental delay vary. In this systematic review, we synthesized the literature on the effectiveness and harms of screening for developmental delay in asymptomatic children aged 1-4 years. METHODS: We searched MEDLINE, Embase and PsychINFO for relevant articles published to June 16, 2015. We identified studies that included children aged 1-4 years who were not at high risk of developmental delay, screened in a primary care setting. Randomized trials and controlled cohort studies were considered for benefits (cognitive, academic and functional outcomes); no restrictions on study design were imposed for the review of harms. RESULTS: Two studies were included. One used the Ages and Stages Questionnaire II for screening and reported significantly more referrals to early intervention in the intervention groups than in the control group (relative risk [RR] 1.95, 95% confidence interval [CI] 1.49-2.54, in the intervention group with office support and RR 1.71, 95% CI 1.30-2.25, in the intervention group without office support). The time to referral was 70% shorter in the intervention group with office support (rate ratio 0.30, 95% CI 0.19-0.48) and 64% shorter in the intervention group without office support (rate ratio 0.36, 95% CI 0.23-0.59), compared with the control group. The other study used the VroegTijdige Onderkenning Ontwikkelingsstoornissen Language Screening instrument to screen children aged 15 months at enrolment for language delay. It reported no differences between groups in academic performance outcomes at age 8 years. INTERPRETATION: The evidence on screening for developmental delay in asymptomatic children aged 1-4 years is inconclusive. Further research with longer-term outcomes is needed to inform decisions about screening and screening intervals.